The effective stress strength parameters of a compacted lateritic soil - Yong, Fook-onn; Richardson, A.M.; Moh, Za-Chieh; Balasubramaniam, A.S.; Asian Institute of Technology (Bangkok : Asian Institute of Technology, 1975)
An investigation to study the shear strength characteristic of saturated and partially saturated compacted lateritic soil was carried out. Conventional isotropically consolidated undrained triaxial compression tests with pore pressure measurements were used in this investigation. To measure the pore water pressure of partially saturated samples, a ceramic stone with high airentry value was used. The soil samples tested were 4 dia x 8'' high and were compacted by adopting modified AASHO standard compaction energy. Three series of test s were carried out. Each series consists of 10 samples, 5 of which were sheared without using back pressure. The three series included (a) soils compacted on the dry side of optimum moisture content having 97 % maximum dry unit weight (b) soil s compacted at optimum moisture content and maximum dry unit weight (c) soils compacted on the wet side of optimum moisture content having 95 % maximum dry unit weight. All series of tests were carried out under effective consolidation pressures ranging from 15 lb/in2 to 120 lb/in2. For pressures above 160 lb/in2 but less than 210 lb/in2, reinforced as well as stainless steel mercury pots were designed and constructed. It was observed that a consolidation pressure of 120 lb/in2 was quite close to the apparent maximum past pressure induced by compaction since all the stress paths at this pressure behaved more or less like an normally consolidated soil. All samples achieved plastic failure. The dilatancy t ends t o increase with decreasing consolidation pressures. Samples tested without back pressuring generally have higher undrained strength than those tested with back pressuring. For test series with back pressure to saturation, samples compacted at optimum moisture content exhibit highest undrained shear strength than those compacted wet and dry of optimum. Whereas for samples tested without back pressuring, those compacted at optimum moisture content tends to have higher undrained strength at low consolidation pressures but samples compacted dry of optimum show to have the highest strength as the consolidation increases. It could be concluded that the lower the void ratio of the sample the higher the undrained strength . The strength envelops of the samples tested without back pressuring tends to fall below from those obtained with the use of back pressure. The gap between the effective strength envelope of saturated samples and to that of unsaturated samples increases with decreasing molding moisture content. It is seen that, saturated sample have higher but lower c than those of unsaturated samples, For unsaturated samples, those compacted at optimum have the highest ~ but the c tends to decrease with increased moisture content. The predicted volume change by using Boyle's and Henry's law is quite agreeable to that of measured volume change during compression tests on un saturated samples. However, possible sources of error s which occured in the test produce have made the prediction of pore air pressure or X value for partially saturated soil impossible .
A thesis submitted in partial fulfilment of the requirements for the degree of Master of Engineering of the Asian Institute of Technology, Bangkok, Thailand.
Thesis (M.Eng.) - Asian Institute of Technology, 1975
Keywords: Soils; Soil stabilization; Shear strength of soils